Bonus losses as consequence of hygienic-sanitary milk quality delivered to the industry from La Pampa dairy farmers (Veterinary Science, 2017)
The decrease of bonus due to quantity and quality of milk remitted to the dairy industry affect significantly the income of an important number of dairy farmers. The objective of the project was to assess the economic losses of the final price of milk as a consequence of a reduced bonus because of compositional, hygiene and sanitary quality as well volume of milk, remitted to the dairy industry, in La Pampa province. Records of volume, quality, hygiene and sanitary quality of 59 dairy farmers of La Pampa were analysed. The basic value of protein without of bonus was obtained through the mean monthly kilogram of protein magnified by the market value of protein. To this value, it was added bonus for colony formed units (CFU), somatic cell counts (SCC), temperature and cryoscopy, and it was compared with the maximum value to obtain in order to determine the losses. The losses in bonus occurred for high SCC and CFU, representing 67 and 33% respectively. Temperature and cryoscopy were not responsible for losses, and temporally the worst months were January, February, June, November and December. The dairy farmers mean monthly losses was 158.252$ equivalent to 2,05% of the income.
Keywords: bonus; milk quality; La Pampa